MMP-2 -1306C > T polymorphism in breast cancer: A case-control study in a South European population - Zagouri, F.; Sergentanis, T.N.; Gazouli, M.; Dimitrakakis, C.; Tsigginou, A.; Papaspyrou, I.; Chrysikos, D.; Lymperi, M.; Zografos, G.C.; Antsaklis, A.; Dimopoulos, M.-A.; Papadimitriou, C.A. (Molecular Biology Reports, 2013)
This case control study aims to investigate the role of MMP-2 -1306C > T polymorphism as a potential risk factor and possible prognostic marker for breast cancer in a South European population. 113 consecutive incident cases of histologically confirmed ductal breast cancer and 124 healthy controls were recruited. MMP-2 -1306C > T polymorphism was genotyped; multivariate logistic regression as well as Cox regression analysis were performed. MMP-2 -1306C > T status was not associated with breast cancer risk either at the total sample or at the subanalyses on premenopausal and postmenopausal women. At the survival analysis, a trend towards a favorable association between MMP-2 -1306C > T allele and disease-free survival as well as overall survival was observed. Regarding subanalyses on ER-negative and ER-positive cases, the favorable association implicating MMP-2 -1306C > T allele was particularly evident among ER-positive cases; no significant associations emerged among ER-negative cases. MMP-2 -1306C > T polymorphism does not seem to be a risk factor for breast cancer in South European population; however, a trend towards a favorable association with survival has been observed. © 2013 Springer Science+Business Media Dordrecht.
Keywords: breast cancer; Case control; MMP-2; MMP-2 -1306C > T polymorphism; Polymorphism